Baseline predictive factors for foregut and hindgut response to long‐term gastric electrical stimulation using augmented energy. Issue 6 (26th October 2021) - Elmasry, Mohamed; Hassan, Hamza; Mathur, Prateek; Stocker, Abigail; Atassi, Hadi; Saleem, Saad; McElmurray, Lindsay; Cooper, Kelly; Hughes, Michael G.; Starkebaum, Warren; Pinkston, Christina; Abell, Thomas
Abstract: Introduction: Gastric electrical stimulation (GES) has been recommended for drug refractory patients with gastroparesis, but no clear baseline predictors of symptom response exist. We hypothesized that long‐term predictors to GES for foregut and hindgut symptoms exist, particularly when using augmented energies. Patients: We evaluated 307 patients at baseline, 1 week post temporary GES, and one year after permanent GES. Baseline measures included upper and lower symptoms by patient‐reported outcomes (PRO), solid and liquid gastric emptying (GET), cutaneous, mucosal, and serosal electrophysiology (EGG, m/s EG), BMI, and response to temporary stimulation. Methods: Foregut and hindgut PRO symptoms were analyzed for 12‐month patient outcomes. All patients utilized a standardized energy algorithm with the majority of patients receiving medium energy at 12 months. Patients were categorized based on change in average GI symptom scores at the time of permanent GES compared to baseline using a 10% decrease over time as the cutoff between improvers versus non‐improvers. Results: By permanent GES implant, average foregut and hindgut GI symptom scores reduced 42% in improved patients ( n  = 199) and increased 27% in non‐improved patients ( n  = 108). Low BMI, baseline infrequent urination score, mucosal EG ratio, and proximal mucosal EG low‐resolution amplitude remained significant factors for improvement status. Conclusions: GES, for patients responding positively, improved both upper/foregut and lower/hindgut symptoms with most patients utilizing higher than nominal energies. Low baseline BMI and the presence of infrequent urination along with baseline gastric electrophysiology may help identify those patients with the best response to GES/bio‐electric neuromodulation. Abstract : 307 patients with gastroparetic symptoms underwent fore and hind gut patient reported outcomes (PRO) evaluation at baseline and after 1‐week temporary and 12‐months of permanent GES. Predictive factors at baseline for improvement with GES at one year included in‐frequent urination, low BMI and high proximal mucosal electrogram amplitude/ low frequency to amplitude mEG ratio. Patients were given nominal energy with temporary GES. Permanent GES patients had factory low energy setting at baseline and most patients with improvement in symptoms had augmented energy at last follow up.